1979
DOI: 10.1007/bf01317891
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the morphology of three coronaviruses

Abstract: The morphology of three coronaviruses, avian infectious bronchitis virus strain Connecticut (IBV Conn), human coronavirus strain 229E (HCV 229E) and mouse hepatitis virus strain 3 (MHV3), were examined by negative staining. Significant differences were found in the sizes of the three coronaviruses. Furthermore, three types of surface projection of the same lengths, but varying widths and morphology, were observed. Both IBV Conn and HCV 229E had bulbous projections characteristic of coronaviruses, although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…Third, mutations in the MHV spike protein that abolish viral-cell fusion activity often map to the HR1 or HR2 residues, which are expected to stabilize the fusion core structure re- (6), but the exact structure of the full-length protein remains unknown. The second state is the prehairpin state of the S2 subunit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, mutations in the MHV spike protein that abolish viral-cell fusion activity often map to the HR1 or HR2 residues, which are expected to stabilize the fusion core structure re- (6), but the exact structure of the full-length protein remains unknown. The second state is the prehairpin state of the S2 subunit.…”
Section: Resultsmentioning
confidence: 99%
“…It binds to the cell surface receptor and mediates subsequent fusion of the viral and cellular membranes (5). Under the electron microscope, the spike proteins can be clearly seen as 20-nm-long surface projections on the virion membrane (6).…”
mentioning
confidence: 96%
“…MHV differs from the prototype coronavirus IBV in a number of respects. For example, Davies & MacNaughton (1979) have reported that IBV has a greater diameter than MHV and that the virus surface projections are morphologically distinct. Also, MHV has a genome that is smaller than IBV (Lai & Stohlman, 1978;Wege et al, 1978;Spaan et al, 1981;Watkins et al, 1975;Lomniczi & Kennedy, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Farklı yapısal özellikleri inceleyen çalışmalara göre coronovirüsler farklı büyüklüklerde (80-120 nm) ve şekillerde küreye benzer şekilde pleomorfik (farklı morfolojik biçimlerde) partiküller oluşturmaktadırlar (5,22,24,25).…”
Section: Coronavirüslerin Genel öZellikleriunclassified
“…Coronavirüslerin 3 farklı gurubu arasında virüslerin yapısında kayda değer farklılıklar bulunmaktadır (22). Coronavirüsler genomlarında genellikle 4 tane yapısal protein kodlamaktadır.…”
Section: Coronavirüslerin Genel öZellikleriunclassified